Analisis Internal Perusahaan (Strength & Weakness), Menggunakan konsep âResource-Based View of the Firmâ dengan Kerangka VRIO - Wandrial, Son (Binus Business Review, 2011)
Problems in the companys internal environmental analysis is to determine the strengths and weaknesses (internal resources), we did not have reasonable grounds to determine whether the companys internal resources as a strength or weakness. Before we can determine whether a resource can be categorized as strengths or weaknesses, we must have a certain criteria so that appropriate resources are said to be a strength or weakness